2020
DOI: 10.1002/ijgo.13084
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of distant metastatic sites in stage IV endometrial cancer: A SEER database study of 2948 women

Abstract: Objective To evaluate the prognosis of women with distant metastasis at the time of endometrial cancer (EC) diagnosis and identify prognostic factors according to metastatic site. Methods A retrospective cohort study of women diagnosed with EC according to the SEER database between 2010 and 2014. Univariate and multivariate Cox regression was used to identify variables associated with overall survival. Kaplan‐Meier curves were used to compare survival among different groups. Results Overall, 2948 women with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…This study found that tumor grade was an independent prognostic factor for OS and CSS, which was consistent with others (16)(17)(18). Our multivariable analysis showed that patients with non-endometrioid and sarcoma subtypes had worse survival than those with endometrioid subtype, consistent with the findings reported by Liu et al (4).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study found that tumor grade was an independent prognostic factor for OS and CSS, which was consistent with others (16)(17)(18). Our multivariable analysis showed that patients with non-endometrioid and sarcoma subtypes had worse survival than those with endometrioid subtype, consistent with the findings reported by Liu et al (4).…”
Section: Discussionsupporting
confidence: 93%
“…Compared with other tumors, bone metastasis is relatively uncommon in EC, with an incidence 0.6% ( 3 ). Among patients in stage IV EC, bone metastasis occurred in 6.8% of patients ( 4 ). Distant organ metastasis usually predicts a poor prognosis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies on distant metastasis in patients with EC, and most of them focus on single metastasis site or specific stage. Liu et al [20] through the study of 2948 patients with stage IV EC from 2010 to 2014, found that the most common metastasis site of stage IV EC was the lung, while the survival rate of patients with brain metastasis was the worst. Ignatov et al [21] described the recurrence pattern of EC according to the risk characteristics through a 7-year follow-up of 2177 EC patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, metastases to distant sites such as the bladder, rectum, ovary, and vagina are common in EC patients. 5 Due to the lack of effective treatment strategies, the 5-year overall survival rate of patients with distant metastatic EC is below 20%. 6 Therefore, novel therapies are needed to further improve patients' survival.…”
Section: Introductionmentioning
confidence: 99%